What is the most appropriate period to define synchronous cancers?. (April 2021) - Baicry, Florent; Molinié, Florence; Plouvier, Sandrine; Colonna, Marc; Daubisse-Marliac, Laetitia; Grosclaude, Pascale; Trétarre, Brigitte; Bara, Simona; Lapôtre-Ledoux, Bénédicte; Woronoff, Anne-Sophie; Guizard, Anne-Valérie; Bouvier, Véronique; et al.
Highlights: The best period to define synchronous multiple primary cancers is 4 months. This period is greater in males (127.8 days) than in females (96.1 days). Estimates of the risk of second primary cancer must consider this definition. Abstract: Background: Studies about second primary cancers (SPC) incidence exclude a period following the first cancer diagnosis given the high probability of diagnosing another primary cancer during this phase (synchronous cancers). However, definition of synchronicity period varies widely, from one to six months, without clear epidemiological justification. The objective of this study was to determine the most appropriate synchronicity period. Methods: Data from 13 French population-based cancer registries were used to establish a cohort of all patients diagnosed with a first cancer between 1989 and 2010. The incidence rate of subsequent cancer was computed by day within 1 year of follow-up after the first diagnosis. Incidence was modelized by joinpoint regression models with an initial quadratic trend and a second constant part (plateau). The joinpoint was the point from which the plateau began and defining the synchronicity period. Results: Our cohort included 696, 775 patients with a first cancer, of which 12, 623 presented a SPC. The median joinpoint for all sites combined was estimated at 120.5 days [112.0−129.0]. Analysis by gender reported a higher difference in 32 days for males (127.8 vs 96.1 days). Noteworthy differences were found depending on patient age and the site of first cancer, with joinpoint ranging from 84.7 (oesophagus cancer) to 250.1 days (bladder cancer). Conclusion: Although some heterogeneity was observed based on the characteristic of the patients, the appropriate synchronicity period appears to be 4 months after the diagnosis of first cancer.